2022
DOI: 10.1109/tvcg.2021.3096494
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Replicas of Real Places: Experimental Investigations

Abstract: The emergence of social virtual reality (VR) experiences, such as Facebook Spaces, Oculus Rooms, and Oculus Venues, will generate increased interest from users who want to share real places (both personal and public) with their fellow users in VR. At the same time, advances in scanning and reconstruction technology are making the realistic capture of real places more and more feasible. These complementary pressures mean that the representation of real places in virtual reality will be an increasingly common us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 30 publications
(23 reference statements)
0
2
0
Order By: Relevance
“…3.7) to contribute to high ecological validity. Skarbez et al [72] showed that a realistic scale of the space is the most important factor for generating a "feeling of reality" [72]. While our setting depicts a "realistic" ATM scenario, there is still a gap to an ATM experience in the wild, which we discuss further in Sect.…”
Section: Methodsmentioning
confidence: 90%
“…3.7) to contribute to high ecological validity. Skarbez et al [72] showed that a realistic scale of the space is the most important factor for generating a "feeling of reality" [72]. While our setting depicts a "realistic" ATM scenario, there is still a gap to an ATM experience in the wild, which we discuss further in Sect.…”
Section: Methodsmentioning
confidence: 90%
“…Slater [69] argued that the effect of both "place illusion" and "plausibility illusion" (PI) can contribute to realistic behaviour in virtual environments and that improved visual realism can enhance realistic behavioural responses [70]. Skarbez et al [67,68] argued that PI is "essentially the extent to which a scenario complies with a user's expectations". As put by Weber et al [80], "there is only little research about the effects of perceived realism in VR and the conducted studies generally show that higher realism goes along with stronger presence".…”
Section: Lessons Learned and Recommendationsmentioning
confidence: 99%